High-entropy metal phosphorus-sulfur compound nanosheet as well as preparation method and application thereof

Through the preparation method of high-entropy metal phosphorus sulfide compound nanosheets, the problem of insufficient catalytic performance of two-dimensional metal phosphorus sulfide was solved and a significant improvement in catalytic performance was achieved. By combining solid-phase synthesis, polar solvent and ultrasonic exfoliation technology, it was prepared Nanosheets with high specific surface area and abundant active sites are produced.

CN119320176AActive Publication Date: 2025-01-17HARBIN INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411446084.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-17
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The catalytic performance of two-dimensional metal phosphorus sulfide is poor, mainly due to the insufficient active site of the base surface, which limits the improvement of catalytic performance.

Method used

The preparation method of high-entropy metal phosphorus-sulfur compound nanosheets is adopted, by solid-phase synthesis of manganese, cobalt, nickel, copper, silver, phosphorus and sulfur elements at a temperature of 590-710°C, combined with polar solvents and ultrasonic peeling technology , to prepare nanosheets with large specific surface area and abundant active sites.

Benefits of technology

The catalytic performance of two-dimensional metal phosphorus sulfide is improved, and the activity and efficiency of the catalyst are significantly improved by combining the surface adsorption performance control of high-entropy alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320176A_ABST
    Figure CN119320176A_ABST
Patent Text Reader

Abstract

The invention provides a high-entropy metal phosphorus-sulfur compound nanosheet as well as a preparation method and application thereof. The preparation method of the high-entropy metal phosphorus-sulfur compound nanosheet comprises the steps that manganese powder, cobalt powder, nickel powder, copper powder, silver powder, phosphorus powder and sulfur powder are mixed according to a preset mass ratio, tableting is conducted after even grinding is conducted, and a tableting sample is obtained; vacuumizing the tableting sample and then packaging the tableting sample; heating the packaged tablet sample to 590-710 DEG C, keeping the temperature for 150-200 hours, and cooling to obtain a block sample; after grinding the block sample, dispersing the block sample in a polar solvent for ultrasonic cleaning to obtain a cleaning mixed solution; taking supernate of the cleaning mixed solution, carrying out ultrasonic crushing treatment, and centrifuging to obtain a nanosheet crude product; and cleaning the nanosheet crude product, and performing vacuum freeze drying to obtain the nanosheet product. The invention aims to solve the problem of poor catalytic performance of metal phosphorus sulfide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanocatalyst materials, and in particular to a high-entropy metal phosphorus-sulfur compound nanosheet, a preparation method and application thereof. Background Art

[0002] Two-dimensional metal phosphosulfide (MPCh3) has become a catalytic platform with application potential due to its high specific surface area and unique electronic structure. However, the basal activity of single MPCh3 is poor and it fails to provide sufficient active sites for the reaction, thus limiting the further improvement of its catalytic performance.

[0003] At present, in order to adjust the activity of the basal plane sites of MPCh3, doping MPCh3 materials with mono- or di-elements is a common material design and preparation strategy. For example, in the related art, B and C doping is used to transform the semiconductor NiPS3 into a metallic state to activate the active sites in the NiPS3 surface. However, the activation performance of a single or simple element combination is limited, which is not conducive to further improving the catalyst performance. Summary of the invention

[0004] The invention aims to solve the problem that the catalytic performance of metal phosphosulfide is relatively poor.

[0005] In order to solve the above problems, the present invention provides a high entropy metal phosphorus-sulfur compound nanosheet and a preparation method and application thereof.

[0006] In a first aspect, the present invention provides a method for preparing high entropy metal phosphorus-sulfur compound nanosheets, comprising:

[0007] The powders of the elements manganese, cobalt, nickel, copper, silver, phosphorus and sulfur are mixed according to a preset mass ratio, ground evenly and then pressed into tablets to obtain a tablet sample;

[0008] The tablet sample is vacuumized and then packaged;

[0009] The encapsulated tablet sample is heated to 590-710°C, kept at this temperature for 150-200 hours, and then cooled to obtain a block sample;

[0010] After grinding the block sample, dispersing it in a polar solvent and performing ultrasonic cleaning to obtain a cleaning mixed solution;

[0011] Taking the supernatant of the washing mixture, subjecting it to ultrasonic crushing treatment, and centrifuging it to obtain a crude nanosheet product;

[0012] The crude nanosheet product is washed and then vacuum-freeze-dried to obtain a nanosheet product.

[0013] Optionally, the powders of the elements are mixed in the following mass proportions: 0.03-0.035 parts of manganese, 0.15-0.2 parts of cobalt, 0.025-0.035 parts of nickel, 0.01-0.025 parts of copper, 0.02-0.035 parts of silver, 0.17-0.19 parts of phosphorus and 0.45-0.55 parts of sulfur.

[0014] Optionally, the temperature rise rate when heating the packaged compressed sample is 1-5°C / min.

[0015] Optionally, the centrifugation comprises:

[0016] The supernatant is first centrifuged at a speed of 3000-4000 r / min, and then the supernatant after centrifugation is centrifuged at a speed of 9000-10000 r / min.

[0017] Optionally, the pressure range of the tablet sample vacuum is 7×10 -4 -9×10 -4 Pa.

[0018] In a second aspect, the present invention also provides a high entropy metal phosphorus-sulfur compound nanosheet prepared based on the above preparation method.

[0019] Optionally, the high entropy metal phosphorus-sulfide nanosheets include the following elements: manganese, cobalt, nickel, copper, silver, phosphorus and sulfur;

[0020] Among them, the molar ratio of manganese, cobalt, nickel, copper, silver, phosphorus and sulfur is (0.1-0.2):(0.1-0.2):(0.1-0.2):(0.1-0.2):(0.1-0.2):1:3.

[0021] Optionally, the thickness of the high entropy metal phosphorus sulfide compound nanosheets is in the range of 1.5-4.5 nm.

[0022] Optionally, the number of layers of the high entropy metal phosphorus sulfide compound nanosheets ranges from 1 to 4 layers.

[0023] In a third aspect, the present invention also provides an application of the above-mentioned high entropy metal phosphorus-sulfur compound nanosheets in electrocatalytic hydrogen evolution reaction and electrocatalytic oxygen evolution reaction.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention performs solid phase synthesis of a variety of high entropy metal elements and phosphorus and sulfur elements at a temperature of 590-710°C, and then uses a polar solvent to preliminarily peel the synthesized bulk sample into a single layer or a few layers of samples. The polar solvent can help the bulk sample overcome the van der Waals force between the layers, thereby preliminarily peeling the bulk sample. Finally, the sample after the preliminary peeling is further peeled by ultrasonic crushing, so that the bulk sample is completely peeled. The completely peeled nanosheet has a large specific surface area and rich active sites, which promotes the performance of catalytic performance. Ultrasonic peeling will cause it to break while reducing the number of nanosheet layers, gradually reducing the lateral size of the nanosheet, shortening the migration distance of electrons between the electrode and the catalyst active site, and achieving the effect of activating the overall catalytic performance. In summary, the present invention prepares high entropy metal phosphorus-sulfur compound nanosheets by solid phase synthesis, solvent, and ultrasonic peeling, and applies a high entropy alloy formed by a variety of metal elements in a specific proportion to a two-dimensional metal phosphorus-sulfide to adjust the basal site activity of the two-dimensional metal phosphorus-sulfide. This combines the advantages of the larger specific surface area of ​​two-dimensional metal phosphosulfide materials and the continuous regulation of surface adsorption properties by high entropy alloys, thereby improving the catalytic performance of two-dimensional metal phosphosulfide materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is an atomic force microscope characterization result diagram of the nanosheet product prepared in Example 1 of the present invention;

[0027] Figure 2 is the XRD pattern of the nanosheet product prepared in Example 1 of the present invention;

[0028] Figure 3 1 is a hydrogen evolution electrochemical characterization diagram of each embodiment and comparative example of the present invention;

[0029] Figure 4 1 is an electrochemical characterization diagram of oxygen evolution of various embodiments and comparative examples of the present invention. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. Although certain embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be interpreted as being limited to the embodiments described herein. On the contrary, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the drawings and embodiments of the present invention are only for exemplary purposes and are not intended to limit the scope of protection of the present invention.

[0031] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by those skilled in the art to which this application belongs; the terms used in the specification of this application are only for the purpose of describing specific implementation methods and are not intended to limit this application;

[0032] The term "including" and its variations used in this article are open inclusions, that is, "including but not limited to"; the term "based on" is "based at least in part on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one other embodiment"; the term "some embodiments" means "at least some embodiments"; the term "optionally" means "optional embodiments". The relevant definitions of other terms will be given in the following description. It should be noted that the concepts of "first" and "second" mentioned in the present invention are used to distinguish different objects, rather than to describe a specific order or a primary and secondary relationship. In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, the meaning of "multiple" is two or more.

[0033] High entropy alloys are a new type of material system that combines multiple elements in equal or approximately equal proportions. Due to their rich elemental composition, high entropy alloys can provide a broad combination space for the design of high-performance catalysts. In addition, high entropy alloys have continuously adjustable adsorption energy, which can optimize the kinetic barriers for the adsorption and desorption of intermediates in the catalytic process. However, high entropy alloys prepared by traditional methods are mostly bulk, and the active sites are difficult to effectively expose, and it is also difficult to use them to improve the catalytic performance of two-dimensional metal phosphosulfides.

[0034] The embodiment of the present invention provides a method for preparing high entropy metal phosphorus-sulfur compound nanosheets, comprising:

[0035] The powders of the elements manganese, cobalt, nickel, copper, silver, phosphorus and sulfur are mixed according to a preset mass ratio, ground evenly and then pressed into tablets to obtain a tablet sample;

[0036] The tablet sample is vacuumized and then packaged;

[0037] The encapsulated tablet sample is heated to 590-710°C, kept at this temperature for 150-200 hours, and then cooled to obtain a block sample;

[0038] After grinding the block sample, dispersing it in a polar solvent and performing ultrasonic cleaning to obtain a cleaning mixed solution;

[0039] Taking the supernatant of the washing mixture, subjecting it to ultrasonic crushing treatment, and centrifuging it to obtain a crude nanosheet product;

[0040] The crude nanosheet product is washed and then vacuum-freeze-dried to obtain a nanosheet product.

[0041] In an embodiment of the present invention, a variety of high entropy metal elements and phosphorus and sulfur elements are solid-phase synthesized at a temperature of 590-710°C. Then, a polar solvent is used to initially peel the synthesized bulk sample into a single layer or a few layers of samples. The polar solvent can help the bulk sample overcome the van der Waals force between the layers, thereby initially peeling the bulk sample. Finally, the sample after the initial peeling is further peeled by ultrasonic crushing, so that the bulk sample is completely peeled. The completely peeled nanosheets have a large specific surface area and abundant active sites, which promotes the catalytic performance. Ultrasonic peeling will not only reduce the number of nanosheets, but also cause them to break, gradually reduce the lateral size of the nanosheets, and shorten the migration distance of electrons between the electrode and the catalyst active site, thereby achieving the effect of activating the overall catalytic performance. Thereby combining the advantages of the large specific surface area of ​​the two-dimensional metal phosphosulfide material and the advantages of the high entropy alloy in the continuous regulation of the surface adsorption performance, the catalytic performance of the two-dimensional metal phosphosulfide is improved.

[0042] Optionally, when preparing high entropy metal phosphorus-sulfur compound nanosheets, the powders of each element can be mixed according to the following mass fractions: 0.03-0.035 parts of manganese, 0.15-0.2 parts of cobalt, 0.025-0.035 parts of nickel, 0.01-0.025 parts of copper, 0.02-0.035 parts of silver, 0.17-0.19 parts of phosphorus and 0.45-0.55 parts of sulfur.

[0043] In this embodiment, the powders of each element are mixed and ground according to the above mass ratio and then tableted. The tableting operation is conducive to the full contact of the powders of each element during the solid phase reaction, thereby improving the reaction efficiency. Finally, a chemically homogeneous product with each metal element in nearly equal proportion can be obtained. While ensuring product quality, the consumption of raw materials can be reduced as much as possible, thereby reducing production costs.

[0044] In some optional embodiments, the compressed sample is packaged after being evacuated, including: placing the compressed sample in a quartz tube and evacuating the tube to a pressure of 7×10 -4 -9×10 -4 Pa, and then use a flame spray gun for packaging. This avoids the interference of other gas impurities and impurities on the solid phase reaction, ensures the uniformity of the high entropy alloy, and obtains excellent mechanical properties and chemical stability.

[0045] In some optional embodiments, when the packaged pressed sample is heated, the heating rate of the pressed sample is 1-5° C. / min. Slow heating is conducive to the uniform growth of the material and avoids the segregation of a single phase.

[0046] In some optional embodiments, after the bulk sample is ground, it is dispersed in a polar solvent for ultrasonic cleaning, and the polar solvent includes an aqueous solution of ethanol or isopropanol, preferably an aqueous solution of ethanol. The polar solvent helps the bulk sample overcome the van der Waals force between layers, thereby preliminarily exfoliating the bulk sample into a few-layer or single-layer sample.

[0047] Optionally, after the ultrasonic treatment, the centrifugal treatment specifically includes: first centrifuging the supernatant at a speed of 3000-4000 r / min, and then taking the supernatant after centrifugation and centrifuging it at a speed of 9000-10000 r / min, so as to remove the large pieces of samples that are not completely peeled off, and ensure that high-quality few-layer or single-layer nanosheets are obtained.

[0048] Optionally, when the crude nanosheet product is washed, it specifically includes: firstly washing the polar solvent remaining on the surface of the crude nanosheet product with an aqueous solution of ethanol, and then washing with water.

[0049] In the second aspect, an embodiment of the present invention provides a high entropy metal phosphorus-sulfur compound nanosheet prepared based on the above-mentioned preparation method, comprising the following elements: manganese, cobalt, nickel, copper, silver, phosphorus and sulfur; wherein the molar ratio of manganese, cobalt, nickel, copper, silver, phosphorus and sulfur is (0.1-0.2):(0.1-0.2):(0.1-0.2):(0.1-0.2):(0.1-0.2):1:3.

[0050] In this embodiment, the high-entropy metal phosphorus-sulfur compound nanosheet contains a variety of high-entropy metal elements in equal proportions or approximately equal proportions, with high overall uniformity. At the same time, the advantages of two-dimensional phosphorus-sulfur compounds and large surface area and the advantages of high-entropy alloys in continuous regulation of surface adsorption properties are combined, so that the catalytic performance of the overall nanosheet is greatly improved.

[0051] Optionally, the thickness range of the high entropy metal phosphorus sulfide nanosheet is 1.5-4.5nm, and the high entropy metal phosphorus sulfide nanosheet is a layered structure with a number of layers ranging from 1-4 layers. Specifically, the main thickness of the nanosheet is distributed in 3-4 layers. At the same time, the sample also contains a single layer of 1-2 layers, and the number of layers is uniformly distributed as a whole. The high entropy metal phosphorus sulfide nanosheet in the embodiment of the present invention is significantly reduced in thickness compared to the bulk sample, and the layered nanosheet has a large specific surface area and abundant active sites. It is beneficial to reduce the size of the material. The prepared nanosheet retains a large number of edge active sites while taking into account the advantages of controllable morphology and number of layers, which promotes the performance of catalytic performance.

[0052] The embodiment of the present invention also provides an application of the high entropy metal phosphorus-sulfur compound nanosheets in electrocatalytic hydrogen evolution reaction and electrocatalytic oxygen evolution reaction.

[0053] The present invention is described in detail below through specific examples and comparative examples.

[0054] Example 1

[0055] This embodiment provides a method for preparing the high entropy metal phosphorus-sulfur compound nanosheets, comprising:

[0056] S1: Mix the powders of the following elements in the following amounts: 0.0325 g manganese, 0.175 g cobalt, 0.03 g nickel, 0.0175 g copper, 0.0275 g silver, 0.18 g phosphorus, and 0.5 g sulfur. After the powders are evenly ground, they are pressed into tablets using a ring-shaped mold to ensure that the elements are fully in contact during the subsequent reaction.

[0057] S2: Place the pressed sample in a quartz tube and evacuate until the pressure inside the tube is 7×10 -4 When Pa, use a flame spray gun for packaging.

[0058] S3: Place the quartz tube in a muffle furnace and heat it to 610°C at a heating rate of 1°C / min. Then keep the quartz tube at 610°C for 168h and cool it with the furnace.

[0059] S4: After grinding the block sample, disperse it in an aqueous solution of ethanol and ultrasonically clean it in an ultrasonic cleaning machine for 2 h.

[0060] S5: Take the supernatant of the mixed solution, further treat it with an ultrasonic crusher for 3 hours, then put the solution into a centrifuge, first centrifuge it at a speed of 3000 r / min, and then take the supernatant after centrifugation and further centrifuge it at a speed of 9000 r / min to obtain a crude nanosheet product.

[0061] S6: The crude product is washed with ethanol and water in sequence, and freeze-dried in a vacuum freeze dryer for 24 hours to obtain a nanosheet product.

[0062] The nanosheet product in this embodiment includes the following elements: manganese, cobalt, nickel, copper, silver, phosphorus and sulfur, wherein the molar ratio of manganese, cobalt, nickel, copper, silver, phosphorus and sulfur is 0.15:0.15:0.15:0.15:0.15:1:3.

[0063] The atomic force microscopy characterization results of the nanosheet product prepared in this example are as follows: Figure 1 As shown, the high entropy metal phosphorus-sulfur compound nanosheets prepared in this embodiment have a thickness range of 1.5-4.5 nm, a layered structure, and 1-4 layers.

[0064] The XRD pattern of the nanosheet product prepared in this embodiment is as follows: Figure 2 As shown, it should be noted that, for the convenience of representation, the chemical formula of the nanosheet products prepared in the embodiments of the present invention is summarized as MnCoNiCuAgPS3. Figure 2 It can be seen that the MnCoNiCuAgPS3 nanosheets prepared in the embodiment of the present invention have a monoclinic crystal structure, indicating that the high entropy material is successfully synthesized without segregation.

[0065] Example 2

[0066] The difference between this embodiment and embodiment 1 is that in the high entropy metal phosphorus-sulfur compound nanosheets of this embodiment, the molar ratio of manganese, cobalt, nickel, copper, silver, phosphorus and sulfur is 0.1:0.1:0.1:0.1:0.1:1:3.

[0067] The preparation method of high entropy metal phosphorus-sulfur compound nanosheets comprises:

[0068] S1: Mix the powders of the following elements in the following quantities: 0.03g manganese, 0.15g cobalt, 0.025g nickel, 0.01g copper, 0.02g silver, 0.17g phosphorus, and 0.45g sulfur. After the powders are evenly ground, they are pressed into tablets using a ring-shaped mold to ensure that the elements are fully in contact during the subsequent reaction.

[0069] S2: Place the pressed sample in a quartz tube and evacuate until the pressure inside the tube reaches 8.5×10 -4 When Pa, use a flame spray gun for packaging.

[0070] S3: Place the quartz tube in a muffle furnace and heat it to 590°C at a heating rate of 3°C / min. Then keep the quartz tube at 590°C for 200 hours and cool it with the furnace.

[0071] S4: After grinding the block sample, disperse it in an aqueous solution of ethanol and ultrasonically clean it in an ultrasonic cleaning machine for 2 h.

[0072] S5: Take the supernatant of the mixed solution, further treat it with an ultrasonic crusher for 3 hours, then put the solution into a centrifuge, first centrifuge it at a speed of 4000 r / min, and then take the supernatant after centrifugation and further centrifuge it at a speed of 10000 r / min to obtain a crude nanosheet product.

[0073] S6: The crude product is washed with ethanol and water in sequence, and freeze-dried in a vacuum freeze dryer for 24 hours to obtain a nanosheet product.

[0074] In this embodiment, high entropy metal phosphorus-sulfur compound nanosheets are successfully synthesized, and the thickness of the nanosheet product ranges from 2 to 4.5 nm, and the layered structure has 1 to 4 layers.

[0075] Example 3

[0076] The difference between this embodiment and embodiment 1 is that in the high entropy metal phosphorus-sulfur compound nanosheets of this embodiment, the molar ratio of manganese, cobalt, nickel, copper, silver, phosphorus and sulfur is 0.2:0.2:0.2:0.2:0.2:1:3.

[0077] The preparation method of high entropy metal phosphorus-sulfur compound nanosheets comprises:

[0078] In step S1 , the element powders are mixed according to the following mass: 0.035 g manganese, 0.2 g cobalt, 0.035 g nickel, 0.025 g copper, 0.035 g silver, 0.19 g phosphorus, and 0.55 g sulfur.

[0079] In step S2, the pressed sample is placed in a quartz tube and vacuumed until the pressure in the tube is 9×10 -4 When Pa, use a flame spray gun for packaging.

[0080] In step S3, the quartz tube is placed in a muffle furnace and heated to 590° C. at a heating rate of 5° C. / min, and then the quartz tube is kept at 710° C. for 150 hours and then cooled with the furnace. The other steps are the same.

[0081] In this embodiment, high entropy metal phosphorus-sulfur compound nanosheets are successfully synthesized, and the thickness of the nanosheet product ranges from 2 to 4 nm, and the layered structure has 1 to 4 layers.

[0082] Comparative Example 1

[0083] The difference between Comparative Example 1 and Example 1 is that in step S1 of the method for preparing high entropy metal phosphorus-sulfur compound nanosheets, the following element powders in mass ratio are mixed: 0.027 g vanadium, 0.03 g manganese, 0.191 g cobalt, 0.032 g nickel, 0.035 g zinc, 0.167 g phosphorus, and 0.518 g sulfur. The other steps are the same.

[0084] Comparative Example 2

[0085] The difference between Comparative Example 2 and Example 1 is that in step S1 of the method for preparing high entropy metal phosphorus-sulfur compound nanosheets, the following element powders in mass ratio are mixed: 0.034 g vanadium, 0.035 g manganese, 0.21 g cobalt, 0.035 g nickel, 0.038 g zinc, 0.173 g phosphorus, and 0.532 g sulfur. The other steps are the same.

[0086] Comparative Example 3

[0087] The difference between Comparative Example 3 and Example 1 is that in step S1 of the method for preparing high entropy metal phosphorus-sulfur compound nanosheets, the following element powders in mass ratio are mixed: 0.038 g vanadium, 0.037 g manganese, 0.24 g cobalt, 0.052 g nickel, 0.04 g zinc, 0.185 g phosphorus, and 0.57 g sulfur. The other steps are the same.

[0088] The nanosheet products prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to electrochemical tests, the test solution was a 1M KOH aqueous solution, the reference electrode was Hg / HgO, and the counter electrode was a graphite rod.

[0089] The electrochemical characterization of hydrogen evolution in each embodiment and comparative example is as follows Figure 3 As shown. Figure 3 It can be seen that the nanosheet products in Examples 1-3 exhibit excellent alkaline hydrogen evolution activity. Specifically, at a current density of 10 mA / cm 2 Under the conditions, the overpotentials of the nanosheet products in Examples 1-3 were -51.8 mV, -60.1 mV, -67.6 mV, and the Tafel slopes were 61.5 mV / dec, 65.7 mV / dec, and 70.9 mV / dec, respectively, compared to -93.3 mV, -122.5 mV, and -187.9 mV in Comparative Examples 1-3, and the Tafel slopes were 76.4 mV / dec, 81.5 mV / dec, and 93.1 mV / dec, respectively, which had a lower overpotential, indicating that the nanosheet products prepared in the embodiments of the present invention have higher catalytic activity in the electrocatalytic hydrogen evolution reaction.

[0090] The electrochemical characterization of oxygen evolution in each embodiment and comparative example is as follows Figure 4 As shown. Figure 4 It can be seen that the nanosheet products in Examples 1-3 exhibit excellent alkaline oxygen evolution activity. Specifically, at a current density of 10 mA / cm 2 Under the conditions, the overpotentials of the nanosheet products in Examples 1-3 were 230 mV, 280 mV, 320 mV, and the Tafel slopes were 83.7 mV / dec, 81.4 mV / dec, 103.2 mV / dec, respectively, compared to 350 mV, 380 mV, and 430 mV in Comparative Examples 1-3, and the Tafel slopes were 170.8 mV / dec, 126.2 mV / dec, and 143.2 mV / dec, respectively, which had a lower overpotential, indicating that the nanosheet products prepared in the embodiments of the present invention have higher catalytic activity in the electrocatalytic oxygen evolution reaction.

[0091] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing high entropy metal phosphorus-sulfur compound nanosheets, characterized in that: include: The powders of the elements manganese, cobalt, nickel, copper, silver, phosphorus and sulfur are mixed according to a preset mass ratio, ground evenly and then pressed into tablets to obtain a tablet sample; The tablet sample is vacuumized and then packaged; The encapsulated tablet sample is heated to 590-710°C, kept at this temperature for 150-200 hours, and then cooled to obtain a block sample; After grinding the block sample, dispersing it in a polar solvent and performing ultrasonic cleaning to obtain a cleaning mixed solution; Taking the supernatant of the washing mixture, subjecting it to ultrasonic crushing treatment, and centrifuging it to obtain a crude nanosheet product; The crude nanosheet product is washed and then vacuum-freeze-dried to obtain a nanosheet product.

2. The method for preparing high entropy metal phosphorus-sulfur compound nanosheets according to claim 1, characterized in that: The powders of the elements are mixed according to the following mass proportions: 0.03-0.035 parts of manganese, 0.15-0.2 parts of cobalt, 0.025-0.035 parts of nickel, 0.01-0.025 parts of copper, 0.02-0.035 parts of silver, 0.17-0.19 parts of phosphorus and 0.45-0.55 parts of sulfur.

3. The method for preparing high entropy metal phosphorus-sulfur compound nanosheets according to claim 1, characterized in that: The temperature rise rate when the packaged compressed sample is heated is 1-5°C / min.

4. The method for preparing high entropy metal phosphorus-sulfur compound nanosheets according to claim 1, characterized in that: The centrifugation comprises: First, the supernatant of the cleaning mixture is centrifuged at a speed of 3000-4000 r / min, and then the supernatant after centrifugation is centrifuged at a speed of 9000-10000 r / min.

5. The method for preparing high entropy metal phosphorus-sulfur compound nanosheets according to claim 1, characterized in that: The pressure range of the tablet sample vacuum is 7×10 -4 -9×10 -4 Pa.

6. A high entropy metal phosphorus-sulfur compound nanosheet prepared by the preparation method according to any one of claims 1 to 5.

7. The high entropy metal phosphorus-sulfur compound nanosheet according to claim 6, characterized in that: These include the following elements: manganese, cobalt, nickel, copper, silver, phosphorus, and sulfur; Among them, the molar ratio of manganese, cobalt, nickel, copper, silver, phosphorus and sulfur is (0.1-0.2):(0.1-0.2):(0.1-0.2):(0.1-0.2):(0.1-0.2):1:

3.

8. The high entropy metal phosphorus-sulfur compound nanosheet according to claim 1, characterized in that: The thickness of the high entropy metal phosphorus-sulfur compound nanosheet is in the range of 1.5-4.5 nm.

9. The high entropy metal phosphorus-sulfur compound nanosheet according to claim 1, characterized in that: The number of layers of the high entropy metal phosphorus-sulfur compound nanosheets ranges from 1 to 4 layers.

10. Use of the high entropy metal phosphorus-sulfur compound nanosheet according to any one of claims 6 to 9 in electrocatalytic hydrogen evolution reaction and electrocatalytic oxygen evolution reaction.

Citation Information

Patent Citations

  • Preparing method and application of NiPS3 nanosheets of self-supporting structure

    CN109772386A

  • Iron-cobalt-phosphorus-sulfur compound micron sheet

    CN111569915A

  • Two-dimensional layered CuInP2S6 semiconductor material and preparation method thereof

    CN112520716A

  • Method for preparing MnPS3 single crystal at low pressure

    CN115558998A

  • Cs + intercalation high-entropy phosphorus sulfide / MXene composite fiber material, preparation method, application and battery

    CN118507674A